Pulp Reduction and Addition of Indigenous Microorganisms as Starter: Effects on Fermented Cocoa Bean Characteristics - Fajariyah, Anna; Rahayu, Endang Sutriswati; Farianti Djaafar, Titiek; Utami, Tyas; Anggraini Suroto, Dian; Marwati, Tri (agriTECH, 2025)
Indonesian cocoa smallholder plantations frequently produced low-quality dry beans due to poor postharvest handling, necessitating improvements through controlled fermentation. This study evaluated pulp reduction and local microorganism starter addition in farmer-level cocoa fermentation on the microbiological, physical, and chemical properties of cocoa beans. Using a Factorial Randomized Block Design, the research included four experimental units: 1) spontaneous fermentation, 2) reduced-pulp fermentation, 3) starteradded fermentation, and 4) reduced-pulp and starter-added fermentation. Pulp was reduced by approximately 35%, and microorganisms utilized were Candida famata HY-37, Lactiplantibacillus plantarum subsp. plantarum HL-15, and Acetobacter sp. HA-37. The five-day fermentation resulted in the growth of yeast, lactic acid bacteria (LAB), and acetic acid bacteria (AAB). This was indicated by a peak fermentation temperature of 45 °C, a decrease in fermentation pH to 3.7, and a decrease in bean pH to 4.7, in line with total titratable acidity increasing. Over the course of two days, the Fermentation Index aboved 1.0. Pulp reduction raised fermentation temperatures and resulted in an earlier peak by the third day. The use of a starter can suppress fungal growth during fermentation. The total fungal population is lower in combining pulp reduction with starter addition fermentation cocoa beans. The physical properties met the Indonesian National Standard (SNI) 2323:2008/Amd I:2010. The chemical characteristics showed that the Fermentation Index was above 1.0, the bean pH values were from 5.16 to 5.36, and the reducing sugar contents were from 1.50 to 1.69 %. Incorporating starter treatment effectively inhibited fungal growth during fermentation. The combination of reducing pulp and adding starter inhibited fungal growth in fermented cocoa beans without affecting their physical and chemical properties.